A Hemispheric and Seasonal Comparison of Tropospheric to Mesospheric Gravity‐Wave Propagation. Issue 18 (13th September 2021) - Alexandre, D.; Thurairajah, B.; England, S. L.; Cullens, C. Y.
Abstract: Deep convection from monsoons has been shown to be a major tropospheric source of gravity waves (GWs) in the summer hemisphere. These GWs can propagate up to the upper mesosphere, either vertically (over the same latitude) or obliquely (latitudinal propagation away from their source), where they dissipate and release their momentum. These waves play an important role in the global dynamical structure of the middle atmosphere. Understanding their hemispheric and seasonal variations could improve the GW parameterization schemes in present global models. To this end, this paper reports on a GW ray‐tracing analysis using the GROGRAT model to simulate the propagation of GWs from the monsoon regions in the northern and the southern hemispheres during both the summer and the winter seasons. The 20 simulations show the southern hemisphere to be more conducive to both the vertical and the oblique propagation of mesospheric GWs compared to the northern hemisphere, regardless of season. This is partially due to a stronger GW filtering in the northern hemisphere near the tropopause where a third of the waves have been vertically reflected. We also show that an increase in the horizontal wavelength increases not only the latitudinal component but also the longitudinal component of the oblique propagation of GWs. The broad spectrum of waves with different horizontal wavelengths and horizontal phase speeds used in this study highlights the existence of an upper limit in the horizontal wavelength of GWs that can reach the upper mesosphere. Plain Language Summary: Atmospheric gravity waves (GWs) propagating through the middle atmosphere play an important role in its global dynamical structure. As the waves propagate upward, the density of the atmospheric background exponentially decreases, resulting in an exponential increase in the wave amplitude and thus the wave energy. GWs from the tropospheric monsoon convection can propagate up to the upper mesosphere where they can break and transfer a significant amount of energy to the background flow. Previous studies have shown the atmospheric coupling between the low‐latitude troposphere and the high‐latitude mesosphere through the oblique propagation of GWs. Using the ray‐tracing model GROGRAT, we first perform a hemispheric comparison of the monsoon‐generated GW propagation between the summer northern hemisphere in July 2016 and the summer southern hemisphere in January 2017. Second, GWs were launched from the same regions but during the winter seasons to study the seasonal differences of this atmospheric phenomenon. The 20 simulations lead to a discussion on the spectral dependencies of the GW propagation and dissipation in the middle atmosphere, and on the nature of the mesospheric GWs in the two hemispheres and the two seasons. Key Points: The vertical reflection of gravity waves at the low‐latitude tropopause is significantly stronger in the northern hemisphere The southern hemisphere appears more conducive to the gravity‐wave propagation from the troposphere to the mesosphere in summer and winter There is an upper limit in the horizontal wavelength relative to the phase speed for gravity waves to reach the upper mesosphere